KONTRIBUSI EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER SISWA DI SD N I PUDING BESAR - Hamdani, Umar (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The background of this study were taken on the basis that the Scouts Contributions Extracurricular Students Character Building in SD N I PudingBesaras the efforts of schools in shaping the character of students through scout activity. This study is a qualitative research, which aims to provide descriptive report obtained from the data collection techniques such as interviews, observation, and documentation. The analysis of data through three stages, namely data reduction, data presentation, and conclusion. The results of this study indicates that the Contributions of Scouts in Students’ character building in SD N I Pudings Besar is significantly effective. It is buildinga good attitude among students, discipline, creative, independent, Love homeland, friendly, care to the environment, more concern with society, responsible, togetherness between each other, Scout activity also has positive influence such as studentsawareness in helpingteachers, more confident, polite and courteous, and innovative